Procesamiento De La Informacion Contable De La Empresa Ingenieria Integrasayox S.A. De La Ciudad De Babahoyo - Guapulema Peñaloza, Leidy Lisseth (2018)
The case study entitled INFORMATION PROCESSING ACCOUNTING COMPANY ENGINEERING INTEGRASAYOX S.A., which is detailed continuation is of great impact and importance for the context of commercial activity business, this document describes information about the accounting process of the company INGENIERIA INTEGRASAYOX S.A. located in the City of Babahoyo, province of Los Ríos, Ecuador, with RUC 0992878665001, is based on a problem detected in this commercial entity in the aspect of the accounting information, In addition, a direct vision is made towards a business environment, taking as an example problematic situations similar to the one dealt with in this topic in relation to what to do accountant. Analyzing the commercial problems from the context of the information that counts The company with this case study, made a direct relationship with the foundations Theoretical researches of different authors and I relate them with the company INGENIERIA INTEGRASAYOX S.A., and identified the lack of knowledge when driving the accounting information